Can we reach the Zeptouniverse with rare K and B_{s,d} decays? - Buras, Andrzej J; Buttazzo, Dario; Girrbach-Noe, Jennifer; Knegjens, Robert (arXiv.org, 2014)
The Large Hadron Collider will directly probe distance scales as short as 10^{-19}m, corresponding to energy scales at the level of a few TeV. In order to reach even higher resolutions before the advent of future high-energy colliders, it is necessary to consider indirect probes of New Physics (NP), a prime example being Delta F=2 neutral meson mixing processes, which are sensitive to much shorter distance scales. However Delta F=2 processes alone cannot tell us much about the structure of NP beyond the LHC scales. To identify for instance the presence of new quark flavour-changing dynamics of a left-handed (LH) or right-handed (RH) nature, complementary results from Delta F=1 rare decay processes are vital. We therefore address the important question of whether NP could be seen up to energy scales as high as 200 TeV, corresponding to distances as small as 10^{-21}m -- the Zeptouniverse -- in rare K and B_{s,d} decays, subject to present Delta F=2 constraints and perturbativity. We focus in particular on a heavy Z' gauge boson. If restricted to purely LH or RH Z' couplings to quarks, we find that rare K decays, in particular KL-> pi^0 nu nubar and K^+->pi^+ nu nubar, allow us to probe the Zeptouniverse. On the other hand rare B_s and B_d decays, which receive stronger Delta F=2 constraints, allow us to reach about 15 TeV. Allowing for both LH and RH couplings a loosening of the Delta F=2 constraints is possible, and we find that the maximal values of M_Z' at which NP effects that are consistent with perturbative couplings could be found are approximately 2000 TeV for K decays and 160 TeV for rare B_{s,d} decays. Finally we present a simple idea for an indirect determination of M_Z' that could be realised at the next linear e^+e^- or mu^+ mu^- collider and with future precise flavour data.